HIGH LEVEL OF PLASMA ALDOSTERONE AFTER SALINE INFUSION TEST IN COMBINATION WITH FINDING OF ADRENAL NODE ON CT SCAN CAN PREDICT ALDOSTERONE-PRODUCING ADENOMA MORE PRECISE THAN FINDING OF NODE ALONE. (April 2021) - Holaj, Robert; Kvasnicka, Jan; Rosa, Jan; Zelinka, Tomas; Petrak, Ondrej; Strauch, Branislav; Kratka, Zuzana; Indra, Tomas; Forejtova, Lubomira; Kavan, Jan; Waldauf, Petr; Widimsky, Jiri
Abstract : Objective: Idiopathic aldosteronism due to bilateral hyperplasia and unilateral aldosterone-producing adenoma of adrenal gland are two main forms of primary aldosteronism. The discrimination between unilateral and bilateral aldosterone overproduction is crucial for an appropriate management of patients with primary aldosteronism. This study tests the reliability of plasma aldosterone after the postural stimulation test and after the saline infusion test in combination with finding of adrenal node on CT scan for the identification of these two common forms of primary aldosteronism. Methods: One hundred and fifty patients with laboratory diagnosis of primary aldosteronism (96 patients with confirmed diagnosis of aldosterone producing adenoma and 54 patients with idiopathic aldosteronism were enrolled into the study. All of patients underwent CT scan, the postural stimulation test, the saline infusion test and adrenal venous sampling. Design and method: Plasma aldosterone concentration in the supine or in the standing position and after the saline infusion were higher in patients with aldosterone-producing adenoma than in those with idiopathic aldosteronism (P < 0.001; P < 0.01 and P < 0.001, respectively). The largest area under the curve = 0.83 (for a cut-off of 165 ng/l) suggesting the diagnosis of unilateral aldosterone overproduction was found for finding of adrenal node on CT scan in combination with plasma aldosterone concentration after the saline infusion test with a sensitivity of 83%, specificity of 61%, positive-predictive value of 79% and negative-predictive value of 67%. Results: The study found that the value of plasma aldosterone concentration ?165 ng/l after the saline infusion test in combination with finding of node on CT scan can predict aldosterone-producing adenoma more precise than finding of node alone, nevertheless, results of adrenal venous sampling remain to be crucial in the identification of two common forms of primary aldosteronism. The study found that the value of plasma aldosterone concentration ?165 ng/l after the saline infusion test in combination with finding of node on CT scan can predict aldosterone-producing adenoma more precise than finding of node alone, nevertheless, results of adrenal venous sampling remain to be crucial in the identification of two common forms of primary aldosteronism.